The Use of Factorization and Multimode Parametric Spectra in Estimating Frequency and Spectral Parameters of Signal - Semenets, V.; Kartashov, V.; Sergiyenko, O.; Tikhonov, V.; Mercorelli, P.; Sheiko, S.; Chmelarova Kudriavtseva, N.; Rodríguez-Quiñonez Julio C.; Flores-Fuentes Wendy (IEEE, 2020)
A multiplicative autoregressive model is constructed based on the linear prediction model. The expressions describing such a model are derived. A formula for the parametric spectral estimation of a random signal multiplicative model is given. Relations are obtained for the decomposition of the multimode power spectral density into simple spectral components. Examples of the decomposition of multimode spectra of random signals into simpler components are considered. Keywords - power spectral density, multiplicative autoregressive model, parametric spectral analysis, characteristic equation.
Keywords: parametric spectral analysis; characteristic equation; power spectral density; multiplicative autoregressive model